Quantitative interactome of a membrane Bcl-2 network identifies a hierarchy of complexes for apoptosis regulation - Stephanie Bleicken (Nature Portfolio, 2017)
The permeabilization of the mitochondrial outer membrane to induce apoptosis is regulated by complex interactions between Bcl-2 family members. Here the authors develop a quantitative interactome of a membrane Bcl-2 network and identify a hierarchy of protein complexes in apoptosis induction.